The cost of international reserves and external debt: Evidence from Malaysia - Mohd Daud, Siti Nurazira; Ahmad, Abd Halim @ Hamilton (2011)
This study aims to empirically examine the cost of Malaysia’s decision to jointly hold reserves and sovereign debt after the 1997 Asian financial crisis. This paper provides evidence that Malaysia should hold international reserves of at least 4.96 months of imports, which is higher than the conventional rule of thumb of 3 months of imports. However, in its current international reserves position Malaysia could finance 9.3 months of retained imports, which is far above the optimal level.